In Vitro Antistaphylococcal Synergistic Effect of Isoflavone Metabolite Demethyltexasin with Amoxicillin and Oxacillin - Rondevaldova, Johana; Hummelova, Jana; Tauchen, Jan; Kokoska, Ladislav (Microbial drug resistance (Larchmont, N.Y.), 2018)
Staphylococcal infections are often hard to treat due to increasing resistance, especially to β-lactams. Previous studies described the synergy between common antibiotics and isoflavonoids; however, little is yet known about the combinatory effects of antibiotics with products of human isoflavone metabolism. In this study, demethyltexasin (DT), a human body metabolite of soybean isoflavones, was evaluated for its possible antistaphylococcal combinatory effect with amoxicillin and oxacillin. For comparison, common therapeutically used combination of amoxicillin/clavulanic acid was tested. DT showed strong synergistic interactions against most of Staphylococcus aureus strains when combined with amoxicillin (sum of fractional inhibitory concentrations [ΣFIC] 0.257-0.461) and oxacillin (ΣFIC 0.109-0.484). When oxacillin was combined with DT, resistance to this antibiotic was overcome in many cases. Moreover, antibiotic/DT combinations were effective mainly against methicillin-resistant S. aureus (MRSA); however, the commonly used drug amoxicillin/clavulanic acid was effective only against sensitive strains. Our results indicated DT as a compound able to act synergistically with β-lactams. In addition, some combinations are effective against MRSA and decrease staphylococcal resistance. To the best of our knowledge this is the first report of the antimicrobial synergistic effects of isoflavone human body metabolite with common antibiotics. DT seems to be a possible candidate for further research focused on antistaphylococcal drug development, especially against antibiotic-resistant strains.
Keywords: Methicillin-Resistant Staphylococcus aureus; antimicrobial combinatory effect; kombinace amoxicilinu a kyseliny klavulanové; Anti-Bacterial Agents; Amoxicillin; checkerboard method; oxacilin; Drug Synergism; Microbial Sensitivity Tests; Amoxicillin-Potassium Clavulanate Combination; Drug Combinations; antibiotic resistance; fixní kombinace léků; Staphylococcus aureus; isoflavony; Methicillin Resistance; synergismus léků; Isoflavones; Humans; amoxicilin; antibakteriální látky; methicilin rezistentní Staphylococcus aureus; β-lactam antibiotics; mikrobiální testy citlivosti; rezistence na methicilin; Oxacillin; lidé